A Delicious Story Made of Chocolate - Rodriguez Medina, Caren; Escobar, Sebastian; Caro Quintero, Alejandro; Yockteng, Roxana (Kids frontiersin, 2024)
Did you know that chocolate is obtained from beans extracted from the fruit of a tree called Theobroma cacao? The fruits are yellow or deep red pods that contain beans covered with a sweet-bitter pulp. Cacao originated in the Amazon region and, for this reason, South America has the highest genetic diversity of the species. The special flavor of each chocolate depends on genetics and the process of transforming cacao seeds into chocolate bars. Cacao cultivation has a fascinating story for which we have to travel through time. The story begins way back with ancient indigenous civilizations that consumed cacao as a drink, and for whom cacao beans were a symbol of power. After the Spanish colonization of the Americas, cacao pods were taken to Europe. In this article, we will learn about the history and importance of cacao for some civilizations, the genetic diversity of cacao species, and the transformation of cacao beans to chocolate.